Detection Of Parasitic Helminth In Gabus Fish (Channa Striata) Natural Catches At Baduk Fish Market Nganjuk Regency - Anita Nur Aida Aida; Setiawan Koesdarto; Emy Koestanti Sabdoningrum; Dian Ayu Permatasari (Universitas Airlangga, 2023)
This study aimed to detect the existence and identify, also to determine the prevalence and degree of infection from parasitic helminth in gabus fish (Channa striata) natural catches at Baduk Fish Market, Nganjuk Regency. In 50 samples of gabus fish, parasitic helminths were examined on the body surface, gills, abdominal cavity, muscles, and digestive tract then identified. Parasitic helminths from digestive tract stained with Semichen Acetic Carmine method. Parasitic helminths that have been identified then calculate the prevalence and degree of infection. The result showed that the parasitic helminths found in gabus fish consist of the genera Pallisentis, Spinitectus, Dactylogyrus, and Gyrodactylus. Pallisentis sp. included in Phylum Acanthocephala, found to infect the intestines with prevalence of 74% and degree of infection of 5,62 parasite each fish. Spinitectus sp. included in Phylum Nematoda, found to infect the stomach and intestines with prevalence of 48% and degree of infection of 8 parasite each fish. Dactylogyrus sp. included in Class Monogenea, found to infect the gills with prevalence of 80% and degree of infection of 1,95 parasite each fish. Gyrodactylus sp. included in Class Monogenea, found to infect the body surface with prevalence of 42% and infection rate of 1,33 parasite each fish.